Immersed to buy: The mediating effect of flow experience on impulsive buying in TikTok live streaming - Rina Sari Qurniawati; Yulfan Arif Nurohman; Riyan Saputra (Priviet Social Sciences Journal, 2026)
Impulsive purchasing tendencies among Generation Z are increasingly shaped by live streaming commerce, which combines promotional incentives, entertainment, and real-time interaction into a digital shopping experience. This study examines the psychological mechanisms underlying impulsive buying behavior among Gen Z consumers in the context of TikTok Live. Using a quantitative survey approach, data were collected through purposive sampling from Generation Z consumers in Salatiga and Semarang who actively watch and shop through TikTok Live. Primary data were gathered using a digital survey and analyzed using PLS-SEM to test the structural relationships in the research model. The findings show that social presence does not directly influence impulsive buying behavior, whereas sales promotion has a significant, direct, and positive effect. However, both social presence and sales promotion significantly affect impulsive buying through the flow experience. Flow experience fully mediated the relationship between social presence and impulsive buying and partially mediated the relationship between sales promotion and impulsive buying. This indicates that immersion, enjoyment, and focused attention during live-streaming sessions increase consumers’ tendency to make spontaneous purchases. This study highlights flow experience as a critical mediating mechanism in Gen Z’s impulsive buying behavior on TikTok Live. The findings suggest that experiential immersion matters more than social cues alone, while sales promotion continues to exert a direct persuasive influence beyond its experiential effect. The main contribution of this study lies in showing that social and promotional stimuli influence impulsive buying differently: social presence requires full experiential mediation, whereas sales promotion retains an independent and direct pathway. These findings enrich the consumer behavior literature by clarifying the conditions under which flow mediates impulsive buying in live streaming commerce. Practically, sellers and content creators should prioritize immersive and engaging live-streaming experiences, while policymakers and researchers should consider experiential factors when examining consumer behavior on emerging social commerce platforms.